Investigation of the potential molecular mechanisms of acupuncture in the treatment of long COVID: a bioinformatics approach: Molecular mechanisms of acupuncture in long COVID - Xu, Ying; Zhong, Jing; Yang, Yang; Xie, Yuequn (Cellular and Molecular Biology, 2024)
Long COVID is a poorly understood condition characterized by persistent symptoms following the acute phase of COVID-19, including fatigue, cognitive impairment, and joint pain. Acupuncture, a key component of traditional Chinese medicine treatment, has shown potential in alleviating long COVID symptoms. However, the molecular mechanisms underlying its therapeutic effects remain largely unknown. In this study, we employed bioinformatics approaches to explore the potential molecular mechanisms of acupuncture's therapeutic effects on long COVID symptoms. We screened protein targets of active ingredients produced by the body after acupuncture and identified potential therapeutic targets of long COVID. Protein-protein interaction networks were constructed, and Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed to identify key targets and pathways. Our findings provide valuable insights into the potential molecular mechanisms of acupuncture's therapeutic effects on long COVID symptoms and may contribute to the development of targeted therapies for managing this challenging condition.